The Role of Humor in Management Response to Positive Consumer Reviews. Issue 2 (May 2022) - Liao, Junyun; Li, Chunyu; Filieri, Raffaele
Marketing managers increasingly monitor their company's online reputation and respond to online consumer reviews on various digital platforms. The current literature provides valuable insights into effectively initiating management response (MR) to negative reviews. However, research on how companies should respond to positive reviews is limited, despite their prevalence in MR practice. In this study, we postulate that using humor in MR for positive reviews can be an effective response strategy to enhance positive attitudinal and behavioral responses. Drawing on parasocial interaction theory, we conducted a field investigation and two experimental studies to demonstrate that humorous ( vs. humorless) MRs to positive reviews fostered perceived parasocial interaction between prospective consumers and brands, which enhanced brand attitude and purchase intention. Furthermore, the proposed effects were stronger for consumers with communal norms than for those with exchange norms. This research advances the emerging literature on MR to consumer reviews of different valences and suggests important guidelines for effective MRs.